2003
DOI: 10.1002/art.11131
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective inhibitor of IκB kinase, BMS‐345541, blocks both joint inflammation and destruction in collagen‐induced arthritis in mice

Abstract: Objective. The transcription of several cytokines, cell adhesion molecules, and enzymes involved in the inflammatory and destructive mechanisms of rheumatoid arthritis is dependent on nuclear factor B (NF-B). Because IB kinase (IKK) is critical in transducing the signal-inducible activation of NF-B, we examined whether the highly selective and orally bioavailable IKK inhibitor BMS-345541 is efficacious against collagen-induced arthritis (CIA) in mice.Methods. Arthritis in DBA/1LacJ male mice was induced by sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
136
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(144 citation statements)
references
References 24 publications
8
136
0
Order By: Relevance
“…In the present study, heparin inhibited NF-κB DNAbinding activity without affecting IκBα degradation or NF-κB nuclear translocation, suggesting that heparin activity occurs in the nucleus, rather than at other upstream levels of the NF-κB activating pathway, such as IκB kinase (McIntyre et al, 2003;Node et al, 1999) and proteasome (Meng et al, 1999;Read et al, 1995). Since heparin is a highly anionic glycosamninoglycan, that it is present in the nucleus of cerebral endothelial cells, and that the NF-κB DNA-binding domain consists largely of basic amino acids (Muller et al, 1995), it seems likely that heparin's anti-inflammatory properties lie in its ability to directly inhibit NF-κB DNA-binding activity (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 45%
“…In the present study, heparin inhibited NF-κB DNAbinding activity without affecting IκBα degradation or NF-κB nuclear translocation, suggesting that heparin activity occurs in the nucleus, rather than at other upstream levels of the NF-κB activating pathway, such as IκB kinase (McIntyre et al, 2003;Node et al, 1999) and proteasome (Meng et al, 1999;Read et al, 1995). Since heparin is a highly anionic glycosamninoglycan, that it is present in the nucleus of cerebral endothelial cells, and that the NF-κB DNA-binding domain consists largely of basic amino acids (Muller et al, 1995), it seems likely that heparin's anti-inflammatory properties lie in its ability to directly inhibit NF-κB DNA-binding activity (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 45%
“…Many groups have demonstrated that inhibition of classical NF-κB, either genetically (deletion of IKKβ) or pharmacologically (NBD peptide, TAT-IκB-super repressor, IKKβ inhibitor), can ameliorate inflammation, and thus the subsequent bone erosion, in models of inflammatory arthritis [12,14,15,60,61]. Unfortunately, the resulting lack of inflammation prevents interpretation of in vivo results with respect to the role of NF-κB specifically in bone cells.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…Understanding the critical signal transduction networks that modulate these host responses has stimulated the development of small molecule inhibitors as promising agents to treat RA (6 -8). For instance, NF-B blockade in RA has focused on the IB kinase (IKK) signal complex, which contains IKK2, as a key convergence point for rapid NF-B activation (9,10). However, systemic inhibition of IKK2 activity poses significant potential safety concerns due to the role of NF-B in host defense and apoptosis.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%